EXAMINING PREPAID RENT AT ARISAN GADAI IN REVIEW OF POSITIVE LAW AND ISLAMIC LAW (CASE STUDY OF PT PEGADAIAN SYARIAH TBK) - Kurnianingsih, Nurinawati; Siddiq, Achmad; Arauf, Muta Ali; Syufa’at, Syufa’at (MIZAN: JOURNAL OF ISLAMIC LAW, 2023)
The mechanism for the practice of gold pawn arisan at sharia pawnshops is increasingly rapid and in great demand, however this is the subject of a new problem in the concept of the application of prepaid rent which is set for the gold pawn arisan products offered. This research aims to understand how Islamic law views the status of down payments in pawn gatherings at the Purwokerto Syariah Pegadaian. The results of this research explain the issues of Sharia economic law on gold pawn products. The problem occurs with the provision of money being paid in advance. Basically, social gathering is a social system that leads to friendship within neighbors and between families. In Islamic Law, debt and receivables are a form of muamalah which is characterized by ta'awun (help) to other parties to meet their needs. Therefore, in this context, someone who provides debt must not take advantage of the goods owed. Debtors may not accept gifts or other benefits from debt borrowers. The money is paid in advance on the guarantee of a gold pawn gathering, which if you intend to help, you should be sincere and not impose additional burdens on returns, but there are business practices. This creates a bad image for Sharia banking if the down payment provisions become a negative thing in Sharia economic law.